Dexamethasone attenuates low-frequency brainwave disturbances following acute seizures induced by pentylenetetrazol in Wistar rats - Rafaella Marques Ribeiro; Esther Padilha da Silveira; Vitoria Corrêa Santos; Leonan Lima Teixeira; Gisely Santiago Santos; Izabela Nascimento Galvão; Maria Klara Otake Hamoy; Allan Carlos da Silva Tiago; Daniella Bastos de Araújo; Nilton Akio Muto; Dielly Catrina Favacho Lopes; Moisés Hamoy (Elsevier, 2024)
Seizures are neurological disorders triggered by an imbalance in the activity of excitatory and inhibitory neurotransmitters in the brain. When triggered chronically, this imbalance can lead to epilepsy. Critically, many of the affected individuals are refractory to treatment. Given this, anti-inflammatory drugs, in particular glucocorticoids, have been considered as a potential antiepileptogenic therapy. Glucocorticoids are currently used in the treatment of refractory patients, although there have been contradictory results in terms of their use in association with antiepileptic drugs, which reinforces the need for a more thorough investigation of their effects. In this context, the present study evaluated the effects of dexamethasone (DEX, 0.6 mg/kg) on the electroencephalographic (EEG) and histopathological parameters of male Wistar rats submitted to acute seizure induced by pentylenetetrazol (PTZ). The EEG monitoring revealed that DEX reduced the total brainwave power, in comparison with PTZ, in 12 h after the convulsive episode, exerting this effect in up to 36 h (p < 0.05 for all comparisons). An increase in the accommodation of the oscillations of the delta, alpha, and gamma frequencies was also observed from the first 12 h onwards, with the accommodation of the theta frequency occurring after 36 h, and that of the beta frequency 24 h after the seizure. The histopathological analyses showed that the CA3 region and hilum of the hippocampus suffered cell loss after the PTZ-induced seizure (control vs. PTZ, p < 0.05), although DEX was not able to protect these regions against cell death (PTZ vs. DEX + PTZ, p > 0.05). While DEX did not reverse the cell damage caused by PTZ, the data indicate that DEX has beneficial properties in the EEG analysis, which makes it a promising candidate for the attenuation of the epileptiform wave patterns that can precipitate refractory seizures.